The Influence of Video-Based Health Education in Modifying Early Screening Efforts for Polycystic Ovary Syndrome (PCOS) - Ni Komang Surya Ariani; Ni Luh Putu Dina Susanti; Ni Wayan Manik Parwati; Ni Putu Sri Haryati (Asian Journal of Health Research, 2022)
Introduction: Polycystic Ovary Syndrome (PCOS) is the most common causes of infertility in reproductive age women. The lack of knowledge about this disease causes PCOS is often late diagnosed. This study aims to determine the influence of health promotion in video-based learning form on young women’s knowledge, attitudes and behaviors in early screening efforts for PCOS. Methods: This is a pre-experimental study with one-group pretest-posttest design. The sample used was 261 female students in one of the senior high schools in Denpasar with a simple random sampling technique. The research instrument used is a questionnaire in which each variable, namely the knowledge, attitude, and the behavioral. The data was analyzed by using the Wilcoxon Rank Test. Results: There was a significant change between the provision of health promotion in the form of video-based learning form on young women’s knowledge, attitudes and behaviors related to the PCOS early screening in each variable, i.e. the knowledge variable p-value = 0.001, the attitude variable p-value <0.001, and the behavior variable p-value <0.001. Conclusion: There was an influence of health promotion in video-based learning form on young women’s knowledge, attitudes and behaviors related to the PCOS early screening.